Nanoparticles in the aquatic environment: Usage, properties, transformation and toxicity-A review - Turan, Nouha Bakaraki; Erkan, Hanife Sari; Engin, Guleda Onkal; Bilgili, Mehmet Sinan (ELSEVIER, 2019)
Nanoparticles are defined as a group of particles having sizes between 1 and 100 nm and characterized by some specific physicochemical properties such as surface area, surface charge, degree of agglomeration, particle morphology and surface coating. Nanoparticles have been widely used in different fields resulting in their intentional or unintentional release into the aquatic environment. This work focused on reviewing the main sources of nanoparticles in the aquatic environment, their interactions and transformation processes. This review also summarizes all the possible toxicity forms and the factors affecting nanoparticles toxicity in the aquatic environment. (C) 2019 Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Nanoparticles; Aquatic environment; Nanoparticles toxicity; Nanoparticles transformations; TITANIUM-DIOXIDE NANOPARTICLES; WALLED CARBON NANOTUBES; ZINC-OXIDE NANOPARTICLES; COATED SILVER NANOPARTICLES; ENGINEERED NANOPARTICLES; TIO2 NANOPARTICLES; OXIDATIVE STRESS; PHYSICOCHEMICAL PROPERTIES; ESCHERICHIA-COLI; PARTICLE-SIZE; Engineering